Knowledge and practices on safe handling, preparation and administration of cytotoxic drug among oncology Nurses (Journal of Namibian Studies : History Politics Culture, 2022)
Nurses, responsible for cytotoxic drugs (CDs) administration, face occupational exposure to these antineoplastic agents. This necessitates nurses to be vigilant and knowledgeable about the CDs' safe handling, ensuring the well-being of patients, themselves, and maintaining a safe working environment. Surprisingly, a gap exists in Palestinian research literature, with no studies evaluating nurses' adeptness in handling these drugs. This study, therefore, seeks to address this void, aiming to gauge the proficiency and practices of oncology nurses in both private and governmental cancer hospitals in Palestine. Positive outcomes from this research could set the foundation for augmenting care quality, enhancing knowledge dissemination, and cultivating best practices among oncology nurses. The insights from the study are somewhat disconcerting, indicating a deficiency in nurses' knowledge and practices concerning CD safety. This gap exists despite a majority having undergone formal training in chemotherapy handling. Distinct differences in knowledge levels were evident when factoring in age and experience duration with CDs. Furthermore, statistical correlations were found between the mean scores of knowledges and practices against variables like age, educational qualifications, and specific CD handling practices like receiving and storing. A silver lining, however, was the frequent usage of protective gear like gloves and masks by nurses during CD handling.